Rozwiązania logistyczne dla funkcji edukacyjnej w pielęgniarstwie = Logistics solutions for educational function in nursing - Ewa Teresa Guz; Dorota Nalepa; Marta Czekirda; Magdaena Brodowicz (Kazimierz Wielki University, 2016)
Guz Ewa, Nalepa Dorota, Czekirda Marta, Brodowicz Magdalena. Rozwiązania logistyczne dla funkcji edukacyjnej w pielęgniarstwie = Logistics solutions for educational function in nursing. Journal of Education, Health and Sport. 2016;6(8):167-180. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.60068 http://ojs.ukw.edu.pl/index.php/johs/article/view/3741       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.07.2016. Revised 25.07.2016. Accepted: 12.08.2016.   Rozwiązania logistyczne dla funkcji edukacyjnej w pielęgniarstwie Logistics solutions for educational function in nursing   Guz Ewa, Nalepa Dorota, Czekirda Marta, Brodowicz Magdalena   Katedra i Zakład Pielęgniarstwa Neurologicznego, Uniwersytet Medyczny w Lublinie Wojewódzki Szpital Specjalistyczny Oddział Neurologii, Uniwersytet Medyczny w Lublinie Zakład Podstaw Pielęgniarstwa i Dydaktyki Medycznej, Uniwersytet Medyczny w Lublinie       Guz Ewa Katedra i Zakład Pielęgniarstwa Neurologicznego 20-954 Lublin ul. K. Jaczewskiego 8 (SPSK Nr 4) Tel. 727920721 ewateresaguz@gmail.com   Nalepa Dorota Wojewódzki Szpital Specjalistyczny Oddział Neurologii Al. Kraśnickie 100 20-718 Lublin tel. 668748836   Czekirda Marta Zakład Podstaw Pielęgniarstwa i Dydaktyki Medycznej 20-081 Lublin ul. S. Staszica 6 (Collegium Maximum) Tel.+48 81448 6800   Brodowicz Magdalena Katedra i Zakład Pielęgniarstwa Pediatrycznego 20-093 Lublin ul. Antoniego Gębali 6 (USzD) +48 81718 5375   Streszczenie Celem pracy jest zaproponowanie rozwiązań logistycznych dla personelu pielęgniarskiego w realizacji funkcji edukacyjnej w oddziałach szpitalnych. By wskazać takie rozwiązania przeprowadzono badania wśród pielęgniarek różnych placówek opieki zdrowotnej a kryterium doboru ankietowanych było wykonywanie pracy w oddziałach takich jak: internistyczny, pediatryczny, geriatryczny, rehabilitacyjny, chorób płuc oraz poradniach przyszpitalnych, gdzie są leczeni pacjenci z astmą oskrzelową. Pielęgniarki propagując działania edukacyjne wpływają na zmianę postaw chorego z biernej na czynną i poprzez to wywierają korzystny wpływ na przebieg choroby. Edukacja chorych w dużej mierze zależy od wiedzy pielęgniarek. Jak pokazały przeprowadzone badania wiele pielęgniarek pracujących z chorymi na astmę nie posiada wystarczającej wiedzy, by prowadzić skuteczną edukację, która zmotywuje do zmiany stylu życia i konkretnych działań na rzecz zapobiegania zaostrzeniom i pełnej kontroli choroby. Po analizie badań zaproponowano konkretne zmiany a jedną z nich jest wyznaczenie konkretnych osób odpowiedzialnych za edukację w danej placówce.   Słowa kluczowe: edukacja, astma, pielęgniarstwo, organizacja pracy. Logistics solutions for educational function in nursing Abstract Aim of study is to suggest logistics solutions for nursing personnel in implementation of educational function in hospital wards. In order to indicate such solutions the research among nurses from different healthcare facilities was conducted. A criterion for the selection of respondents was performance of work in different wards such as: internal medicine, pediatric, geriatric, rehabilitation, lung diseases and clinics where the patients with bronchial asthma are treated. Nurses who popularize educational activities influence the change of sick person's attitude from passive to active and as the result they have a positive impact on course of the disease. Education of sick ones depends on nurses' knowledge to a great extent. As the research showed, many nurses working with patients with asthma do not have enough knowledge to effectively educate them. Yet, this education should motivate patients to change their life styles, to take specific actions preventing from exacerbations and to fully control the disease. After analysis of research, specific changes were suggested and one of them was to designate specific persons responsible for education in a particular healthcare facility.   Key words: education, asthma, nursing, labor organization.